2016
DOI: 10.1002/ldr.2551
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Impact of Coppice Management on Soil in a Quercus ilex l. Stand of Sardinia

Abstract: The short-term impact of coppice-with-standards management on soil in a Mediterranean holm oak forest was assessed to contribute to address appropriate recommendations to minimize possible negative effects of the silvicultural practices. For this purpose, soil surface features and topsoil properties were investigated in two representative areas located in a public forest in southwest Sardinia (Italy) and coppiced in the periods November 2012-March 2013 and November 2011-March 2012, respectively. Regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…With regard to the thickness of the surface horizons, shown in Tables 2 and 4 in Vacca et al (), only a decrease in litter thickness is reported, whereas the thickness of horizon‐A is uniform in all plots (both cut and undisturbed) in both the S'Isteri (average: 6.75 cm; SD : 5.85) and Su Caraviu (average: 21.92 cm; SD : 5.7) stands. The high standard deviation of S'Isteri is due to two particularly high values of soil thickness (15 and 22 cm) detected in the area undergoing coppice cutting (Figure ).…”
Section: Interpretation Of the Findingsmentioning
confidence: 93%
See 4 more Smart Citations
“…With regard to the thickness of the surface horizons, shown in Tables 2 and 4 in Vacca et al (), only a decrease in litter thickness is reported, whereas the thickness of horizon‐A is uniform in all plots (both cut and undisturbed) in both the S'Isteri (average: 6.75 cm; SD : 5.85) and Su Caraviu (average: 21.92 cm; SD : 5.7) stands. The high standard deviation of S'Isteri is due to two particularly high values of soil thickness (15 and 22 cm) detected in the area undergoing coppice cutting (Figure ).…”
Section: Interpretation Of the Findingsmentioning
confidence: 93%
“…The high standard deviation of S'Isteri is due to two particularly high values of soil thickness (15 and 22 cm) detected in the area undergoing coppice cutting (Figure ). Data related to organic carbon content in horizon‐A that are reported in Tables 2 and 4 in Vacca et al () show no significant differences between the covered and cut areas (S'Isteri: average = 11.1%, SD = 3.4%; Su Caraviu: average = 9.6%, SD = 2.3%; Table ). The values of organic carbon content in Table 5 (Vacca et al, ) seem to be derived (not reported) from the aggregated analysis of the surface soil (horizon‐A) and litter (horizon‐O).…”
Section: Interpretation Of the Findingsmentioning
confidence: 95%
See 3 more Smart Citations